Question -
Answer -
(c) 16= 4 + 3 (t + 2)
⇒ 16 – 4= 3(t + 2) (Transposing 4 to LHS)
⇒ 12 = 3(t + 2)
⇒(Dividingboth sides by 3)
⇒ 4 = t+ 2
⇒ 4 – 2= t (Transposing 2 to LHS)
⇒ 2 = tor t = 2
Check: Put t = 2 in RHS
4 + 3(2 + 2) = 4 + 3 × 4 = 4 + 12
= 16 LHS as required
(d)4 + 5(p – 1) = 34
⇒ 5(p –1) = 34 – 4(Transposing 4 to RHS)
⇒ 5(p –1) = 30
⇒ (Dividing bothsides by 5)
⇒ p – 1= 6
⇒ P = 7
Check: Put p = 7 in LHS
4 + 5(7 – 1) = 4 + 5 × 6
= 4 + 30 = 34 RHS as required
(e) 0 = 16 + 4(m – 6)
⇒ 0 — 16= 4(m – 6) (Transposing 16 to LHS)
⇒ -16 =4(m – 6)
⇒ (Dividing both sides by 4)
⇒ -4 = m– 6
⇒ -4 + 6= m (Transposing 6 to LHS)
⇒ 2 = m
or m = 2
Check: Put m = 2 in RHS
16 + 4(2 – 6) = 16 + 4 × (-4) = 16 – 16 = 0 LHS as required